Relationship of betatrophin with youth onset type 2 diabetes among Asian Indians. Issue 1 (July 2015) - Gokulakrishnan, Kuppan; Manokaran, Kalaivani; Pandey, Gautam Kumar; Amutha, Anandakumar; Ranjani, Harish; Anjana, Ranjit Mohan; Mohan, Viswanathan
Highlights: We studied betatrophin levels and their association with youth-onset T2DM individuals. Betatrophin levels were significantly lower in T2DM-Y compared to NGT group. Betatrophin is negatively correlated with insulin resistance and fasting glucose. Betatrophin shows a positive correlation with the oral disposition index. Betatrophin was associated with T2DM-Y but lost significance when adjusted for HOMAIR. Abstract: Background and Aims: Betatrophin is emerging as a marker for compensatory beta cell proliferation. While betatrophin has been mainly investigated in adults, there is a lack of data on betatrophin levels in youth-onset type 2 diabetes mellitus (T2DM-Y). The aim of this study was to determine levels of betatrophin and its association with T2DM-Y in Asian Indian participants. Methods: We recruited 100 individuals with normal glucose tolerance (NGT; n = 50) and newly-diagnosed cases (within 18 months of first diagnosis) of T2DM-Y ( n = 50) with onset between 12 and 24 years of age from a large tertiary diabetes center in Chennai in southern India. Insulin resistance was measured by homeostatic model (HOMA-IR) and insulin secretion by oral disposition index (DIO). Betatrophin levels were measured by enzyme-linked immunosorbent assay. Results: Betatrophin levels were significantly lower in the T2DM-Y group compared with the NGT group (803 vs 1104 pg/ml, p < 0.001). Betatrophin showed a significant inverse correlation with waist circumference ( p = 0.035), HOMA-IR ( p < 0.001), fasting and 2 h postprandial glucose ( p < 0.01), glycated hemoglobin ( p = 0.019) and a positive correlation with fasting C-peptide ( p < 0.001) and DIO ( p = 0.012). In regression analysis, betatrophin was independently associated with T2DM-Y even after adjustment for age, gender, and waist circumference (OR per standard deviation: 0.562, 95% CI: 0.342–0.899, p = 0.019). However, the association was lost when HOMA-IR was included in the model (OR: 1.141, 95% CI: 0.574–2.249; p = 0.646). Conclusion: Betatrophin levels are lower in T2DM-Y and this association is likely mediated through insulin resistance.